Effect of Different Combination of Organic and inorganic Fertilizer on Growth and Yield of Onion Under Protected Condition - Thapa, Diksha M.; Kafle, Astha; Sinha, Sugandha; Rajput, Shivam S.; Yadav, Jayram; Shrestha, Abhisek (Journal of Agriculture and Resource Management, 2026)
Onion productivity in Nepal remains below the global average, largely due to imbalanced and inefficient fertilizer management. To address this, a field experiment was conducted under protected conditions at the College of Natural Resource Management (CNRM), Bardibas, Mahottari, to evaluate the effect of different combinations of organic and inorganic fertilizers on the growth and yield of onion (Allium cepa L.) cv. ‘Nasik Red’. The experiment was carried out in Completely Randomized Design with eight treatments: control, 100% inorganic nitrogen + 100% FYM, 100% FYM, 100% vermi compost, 50% inorganic nitrogen and 50% FYM, 50%inorganic nitrogen + 25% FYM + 25% vermi- compost, 25% inorganic nitrogen + 75% FYM, 25% inorganic nitrogen + 75% vermi- compost with three replications. Growth parameters (plant height, leaf number and chlorophyll content) and yield attributes (bulb weight, bulb diameter, biomass and yield) were recorded and statistically analyzed using ANOVA at a 5% significance level. Results revealed that fertilizer treatments significantly influenced plant height, bulb weight, and total yield, whereas effects on leaf number, chlorophyll content, bulb diameter and harvest index were statistically non-significant. The highest plant height (62.92 cm), bulb weight (43.6 g), and maximum yield (15.36 t ha⁻¹) were obtained with 100% vermicompost, followed closely by 25% inorganic N + 75% FYM. The control treatment consistently recorded the lowest values for all growth and yield parameters. However, economic analysis showed that despite superior biological performance, 100% vermicompost had the lowest benefit–cost ratio (0.38) due to high input costs. In contrast, 100% FYM exhibited the highest economic return (B:C = 2.66). The study concludes that while vermicompost enhances onion productivity under protected conditions, 100% FYM is the most economically viable option in soils with adequate native nitrogen and phosphorus. The findings highlight the importance of integrated nutrient management for sustainable and profitable onion production in Nepal. It can be further tested in farmer field for validation and recommendation.